DEVELOPMENT OF MOTOR SKILLS OF CHILDREN WITH DYSARTHRIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents the contents of the corrective work carried out on the development of the field of movement of children with dysarthria speech deficiency, the goals and objectives of the educational experiment conducted to improve the effectiveness of the correctional work, the results of the conducted educational experiment, and pedagogical recommendations for pedagogues and parents.